(untitled) (American Journal of Arts and Human Science, 2022)
This present study aims to determine the relationship between Knowledge, Skill, Attitude and Team Performance of a Chorale Group. The respondents of this study are the members of Tinig Angeleño at A Local City College. There are two questionnaires that were used: The Team Performance Scale and The KSA Questionnaire. The KSAQ was formulated for the study and underwent pilot testing to non-Chorale Group students (N=73) with (α =.885, .810 and .896) which confirms that the instrument can be used for the study; while TPS was used to describe the overall team performance of the group. Mean and Standard Deviation were used to describe KSA and Team Performance while Spearman’s rho was used to determine the relationship between KSA and Team Performance. After data were gathered from 15 members of the Chorale Group it was found out that the KSA and team performance of the chorale members is high. In regards to the relationship between KSA and Team Performance, it was found out that there is a significant relationship between Attitude and Team Performance, while there was no significant relationship observed to the knowledge and skill of members to their team performance. From the obtained results, it is highly recommended to conduct studies regarding the relationship of knowledge, skills, and attitude with team performance to a larger population, not only in a vicinity of the college. These results provide new information to the students and experts who have an interest in conducting the same study. Further investigation in this research study is highly recommended.